The association between mood and anxiety disorders, and coronary heart disease in Brazil: a cross-sectional analysis on the Brazilian longitudinal study of adult health (ELSA-Brasil) - Kemp, Andrew H.; Brunoni, Andre R.; Nunes, Maria A.; Santos, Itamar S.; Goulart, Alessandra C.; Ribeiro, Antonio L.; Benseñor, Isabela M.; Lotufo, Paulo A. (Frontiers in Psychology, 2015)
Background: Associations between major depressive disorder and coronary heart disease (CHD) have been established, and these associations increase risk of future morbidity and mortality. Prior research has been carried out in high-income countries. Here we examine associations between the mood and anxiety disorders, and coronary heart disease in a large cohort at baseline from Brazil, a country facing a variety of challenges that may affect these associations. Methods: Participants included 15,105 civil servants aged 35 to 74 at baseline (2008-10) from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). CHD (N=721) included self-reported angina pectoris (n=305), myocardial infarction (MI) (n=259) and coronary revascularization (n=239). Hierarchical logistic regression analyses were conducted to estimate odds ratios and confidence intervals. Results: Major findings indicate that comorbid major depressive disorder and anxiety disorders (n=434) are associated with a 3-fold increase in CHD, major depressive disorder alone (n=170) with a 2-fold increase in CHD, while generalised anxiety disorder alone (n=1,394) and mixed anxiety and depression disorder (MADD; n=1,844) – symptoms present, but diagnostic threshold not reached – are associated with a 1.5-fold increase in CHD, after full adjustment for covariates. Conclusions: The association with CHD is greatest in those with psychiatric comorbidity, while associations were also observed in major depressive disorder and generalised anxiety disorder without comorbidity. While findings are limited by the cross-sectional design of the study, given the known risks associated with comorbidity of the mood and anxiety disorders with CHD, findings reinforce the importance of comprehensive health assessment in Brazil.